Determination of Shipping Safety by Maintenance, Ship Construction, Weather, and Human Resource Competence: In a Literature Review - Yuliantini Yuliantini; Muhammad Thamrin; Primadi Candra Susanto (Dinasti Publisher, 2024)
This article aims to provide a more holistic and in-depth insight into the factors that determine shipping safety and provide a basis for developing more effective strategies and policies in the maritime sector. A qualitative method by exploring and understanding how factors such as maintenance, ship construction, weather, and human resource competence affect shipping safety. Relevant literature sources come from reputable journals that analyze the literature's findings by providing researchers' perspectives. In addition to adding insight from the results of this article, it can be concluded that the effective implementation of human resource competence, monitoring and management of weather and technological risks, as well as in-depth analysis of the factors that cause accidents, are the keys to improving shipping safety. An emphasis on continuous training, adaptation to new technologies, and thorough risk evaluation will help in creating a safer and more efficient shipping environment.